The “Dialogue” Between Central and Peripheral Immunity After Ischemic Stroke: Focus on Spleen - Yu, Hongchen; Cai, Yichen; Zhong, Aiqin; Zhang, Yunsha; Zhang, Junping; Xu, Shixin (Frontiers in Immunology, 2021)
The immune response generated by the body after the incidence of ischemic stroke, runs through the comprehensive process of aftermath. During this process of ischemic stroke, the central neuroinflammation and peripheral immune response seriously affect the prognosis of patients, which has been the focus of research in recent years. As this research scenario progressed, the "dialogue" between central nervous inflammation and peripheral immune response after ischemic stroke has become more closely related It's worth noting that the spleen, as an important peripheral immune organ, plays a pivotal role in this dialogue. Multiple mechanisms have previously been reported for brain-spleen crosstalk after ischemic stroke. Further, neuroinflammation in the brain can affect the peripheral immune state by activating/inhibiting spleen function. However, the activation of the peripheral immune inflammatory response can work reversibly in the spleen. It further affects intracerebral neuroinflammation through the injured blood-brain barrier. Therefore, paying close attention to the role of spleen as the pivot between central and peripheral immunity in ischemic stroke may help to provide a new target for immune intervention in the treatment of ischemic stroke. In the present review, we reviewed the important role of spleen in central neuroinflammation and peripheral immune response after ischemic stroke. We summarized the relevant studies and reports on spleen as the target of immune intervention which can provide theoretical basis and new ideas for the clinical treatment of ischemic stroke.